Investigation of the properties of core spun yarn containing a metal wire - (:unkn) unknown (Fiber Society, 2012)
In this study, core spun yarns (core part copper, outer part cotton) at three different yarn counts and in three different twist degrees were manufactured in a laboratory type ring spinning machine. Every yarn type contains the same size copper wire (60 μ). But the outer layer (cotton) amount was changed. The effect of the cotton amount on the tensile properties, twist, yarn count, hairiness and electrical resistance were investigated.
Keywords: Copper wire; Core spun yarn; Electrical resistance